PENGARUH PROBLEM BASED INSTRUCTION (PBI) TERHADAP KEMAMPUAN SISWA DALAM MENYELESAIKAN MASALAH PENCEMARAN LINGKUNGAN - SUGIATI, IIS (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
This research purposed to determine effect of the application of Problem Based Instruction (PBI) model toward ability student’s in solving of environmental pollution problems.This research was a Pre Experimental Design using the One Group Pretest-Posttest Design. Data of the student’s ability to solve problems collected using pretest and posttest methods of assessment with average reliability was 0.78. Test data were analyzed using the technique of Spearman rank correlation (α=5%) followed by calculating the determination coefficient. The results of research showed that there are 98,01% influence which was positive and significant between application of models PBI against ability of students in solving environmental pollution problems, with value of RS=0,99 (very high) and ZH (12.69) > Z table (0.96). Keywords: implementation of PBI, the students ability to solve the problem of environmental pollution